Report of the nineteenth annual Trades union congress : held in the Bethel lecture hall, Sykes street, Hull, on september 6, 7, 8, 9, 10, and 11, 1886 - Trades union congress (19 ; 1886 ; Hull)
Published by the authority of the Congress and the Parliamentary committee